Self Expressions : Mind, Morals, and the Meaning of Life. - Flanagan, Owen (Oxford University Press, 1998)
Continuing the project of reconciling a scientific view with the view of ourselves as agents of free will, this collection of essays explores scientific explanation of consciousness, the moral socialization of children, and, nature and issues of psychology such as multiple personality disorder.